1997
DOI: 10.1086/303939
|View full text |Cite
|
Sign up to set email alerts
|

Karhunen‐Loeve Eigenvalue Problems in Cosmology: How Should We Tackle Large Data Sets?

Abstract: Since cosmology is no longer "the data-starved science", the problem of how to best analyze large data sets has recently received considerable attention, and Karhunen-Loève eigenvalue methods have been applied to both galaxy redshift surveys and Cosmic Microwave Background (CMB) maps. We present a comprehensive discussion of methods for estimating cosmological parameters from large data sets, which includes the previously published techniques as special cases. We show that both the problem of estimating severa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
1,156
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,004 publications
(1,163 citation statements)
references
References 36 publications
6
1,156
0
1
Order By: Relevance
“…We closely follow the derivation of the Fisher matrix presented in Tegmark et al (1997). A comma notation is used to indicate derivatives with respect to parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We closely follow the derivation of the Fisher matrix presented in Tegmark et al (1997). A comma notation is used to indicate derivatives with respect to parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Since T is invertible, the data in x and y contains the same amount of information about the parameters. Accordingly, the Fisher matrix is also invariant under this transformation (Tegmark et al 1997), which is easily demonstrated by inserting (26) into (25). However, in the case of nulling the transformation (19) to the new data vector Π (i) ( ) depends on the cosmological parameters one aims at determining because the elements of T are composed of comoving distances.…”
Section: Fisher Matrix Formalismmentioning
confidence: 99%
See 1 more Smart Citation
“…(16), (18) and the finite difference derivatives for Eq. (17) from the simulated WL maps -one can use the Fisher matrix formalism ( [67], and see [68] and [69] for comprehensive reviews of this application) to compute parameter constraints. In fact, at least four groups have followed this approach recently for weak lensing simulations, some with redshift tomography [53][54][55]70].…”
Section: B Parameter Estimation and Constraintsmentioning
confidence: 99%
“…Our original motivation for applying a PCA (following Vogeley & Szalay 1996 ;Tegmark, Taylor, & Heavens 1997) was to allow optimal compression of the data into the modes that are most important for estimating the parameters we wish to evaluate, with the aim to reduce the computational cost associated with inverting huge correlation matrices and to improve the results given an inaccurate correlation matrix. In the current paper we use a PCA for two other purposes.…”
Section: Principal Component Analysismentioning
confidence: 99%